التراث النقدي والبلاغي في ضوء مناهج التحليل - كتانة, حسين أحمد حسين (Revues faculté des lettres et des langues; No 9 (2011): مجلة كلية الآداب واللغات, 2014)
يعتبر المشروع النقدي للعلامة أحمد الطرابلسي أحد أبرز و أهم المشاريع العلمية التي توسلت برؤية منهجية دقيقة و عميقة في مراقبة المنجزات النظرية و المنهجية للنقاد العرب القدامى، و يلاحظ القارئ لكتابه " نقد الشعر عند العرب " أن تميزه عن غيره من المؤلفات المتزامنة معه و المعاصره له يعود إلى توسل صاحبه بالمنهج الحفري المندمج ، و أن هذا المنهج مكنه من الكشف عن مسارات تشكل النقد العربي و تطوره ، و إبراز مسافات اشتغال مفاهيمه و تداول أحكامه و تصوراته، دون تعصب للتراث أو تنقيص منه .   The scholar Amjad At-Trabulsy criticism project is deemed one of the most accurate.in-depth . and methodologically sound projects in the field . particulary in setting the pillars of the the theoretical and methodological finding of the ancient Arab critics .Reading At-Tarabulsy’s The Criticism of Poetry according to the Arabs .one can detect its distinction from the many published critical treaties of its time. A distinction attributed to At-Tarabulsy recruitment of an excavation method of critical inquiry.This methodology enabled him uncover the tracks of the development of Arabic literary criticism and objectively underline the visions adopted and the domains trageted by such criticism . without any bias for or against tradition.